Algirdas Penkauskas (1931-1985). Asmenybė, pedagogas, mokslininkas - Dzikarienė, V.; Dževečka, A.; Garbačiauskienė, M.; Kregždė, S.; Krukovskis, J.; Kulvičienė, A. (Psichologija, 1987)
Straipsnyje pristatoma Algirdo Penkausko biografija, jo esminiai darbai.